Pengaruh Metode Ceramah dan Metode Tanya Jawab Terhadap Minat Belajar Siswa Pada Mata Pelajaran Al-Qur’an Hadis di MAN Bangkalan - Sulaiman, Ibnuh; Hasan, Musohihul (Ar-Rusyd: Jurnal Pendidikan Agama Islam, 2024)
The purpose of this study was to determine whether there was an influence and the amount of influence of the lecture method and question and answer method on the learning interests of students in classes XI AGAMA and XI BAHASA in al-qur’an hadis subjects at Madrasah Aliyah Negeri Bangkalan in the 2022–2023 school year. This research is a population study with a total of 34 respondents using a quantitative survey model. The main instrument for data collection is a questionnaire. Data that meets and passes the validity and reliability tests and classical assumption tests is then analyzed using the F-Test on Multiple Linear Regression using the IBM SPSS Statistics 21 program, which produces the following equation: Ŷ = 8,390 + 0,382 + 0,383. The results show that Fcount 19.269 > Ftable 3.30 df = 2; df2 = 31 at the 5% significance level, which indicates that the lecture method and question and answer method simultaneously affect student interest in learning. R Square 0.554 means that the lecture method and question and answer method variables have a contribution of 55.4% to the student learning interest variable. While the rest is influenced by other variables that are not in the study. The R Square value of 55.4% can be classified as having a moderate/moderate influence on the dependent variable based on Chin's theory.